Identification of the Issues for Successful Collaboration Between Malaysia and Japan: Synergising Defense Manufacturing Capabilities - MALARVIZHI, CHINNASAMY; JAYASHREE, SREENIVASAN; MANZOOR, SHAMIMA RAIHAN (International Journal of Psychosocial Rehabilitation, 2020)
For several decades, the emphasis of the Malaysia-Japan relationship centred on economic cooperation, but the two countries’ ties gradually “expanded to include culture, tourism, education and security”. Recent developments at both domestic and international levels could pave the way towards a stronger, deeper and more comprehensive relationship. These changes are observable in the bilateral relations between Malaysia and Japan. While economic ties are still the focus of Malaysia-Japan relations, recent developments — through various initiatives and agreements in the last ten years — suggest that “the two countries are keen not only on reviving and reaffirming their ties but also on expanding cooperation in other areas as well”. One of these includes strengthening the capabilities in the defense and security sector in Malaysia. Both countries vowed continued cooperation and commitment to maintaining security in various areas such as the Korean Peninsula, the Middle East, and Southern Philippines; peacebuilding; maritime navigation; and the global fight against terrorism.This study intends to identify the possible strengths and opportunities of both Malaysia and Japans’ defense manufacturing industry and outline necessary strategies for successful collaboration to strengthen the defense manufacturing capabilities for Malaysia. The assessments shown in this study is expected to generate meaningful insights for the defense manufacturing companies, when there are powers competing in the region for military supremacy as well as global economic uncertainties, a closer Malaysia-Japan defense collaboration could produce synergistic impact for both countries. The confidence and the trust that have grown in recent years between the two countries in the overall bilateral relationship “have facilitated the strategic/security partnership in which the defense industry ties would be a key component of the ongoing ‘Japan-Malaysia strategic partnership’”